Efficacy of secnidazole in the treatment of trichomoniasis and vaginal dysbiosis - V. F. Bezhena; O. L. Molchanov; N. B. Lazareva; L. A. Galiullina; A. L. Poznyak (Медицинский совет, 2022)
Introduction. Trichomoniasis is a vaginal infectious and inflammatory disease, which falls into the category of sexually transmissible nosological entities. It is the profile of vaginal microecosystem changes in trichomoniasis that determines the vector of transformation of the vaginal microbiome towards the formation of bacterial vaginosis (BV), namely, a hypercolonized community of anaerobic microorganisms with underlying suppression of the dominant presence of the resident acidophilic microflora.Aim. To evaluate the clinical and bacteriological efficacy of 5-nitroimidazole drugs secnidazole and metronidazole in the therapy of acute trichomoniasis and concomitant vaginal dysbacteriosis.Materials and methods. As a comparison object, we used the therapy regimens for acute trichomoniasis with the 5-nitroimidazole drugs secnidazole and metronidazole, involving 2 grams (g) once as a single dose. The study included 64 patients diagnosed with acute trichomoniasis. The average age of the patients was 34 ± 7 years (95% CI 32–37). The patients were divided into two groups: group 1 (n = 32) used Secnidazole, group 2 (n = 32) used Secnidazole 2 g once as a single dose. Metronidazole was used at a dose of 500 mg 2 times a day for 5 days. Patients were observed by a doctor during two visits, and a follow-up assessment of the treatment results was carried out by way of remote interrogation.Results. The use of the drug therapy ensured removal of Trichomonas from the vagina. Both groups showed relief of clinical symptoms from B1 to B2: discomfort, itching, burning, dyspareunia, hyperemia of the mucosa with underlying tendency towards normalization of laboratory findings of the vaginal microbiocenosis condition. At the same time, it should be noted that the therapy efficiency was higher in group 1 (secnidazole).Conclusion. Thus, the administration of secnidazole provided greater therapeutic efficacy as compared with the use of the similar therapeutic dose and frequency of metronidazole to treat Trichomonas and, in combination with rehabilitation therapy, determined a more pronounced tendency towards normalization of the composition of the vaginal microflora.